THE ROLE OF LEADING SECTOR IN REALIZING INCLUSIVE ECONOMIC DEVELOPMENT IN NORTH CENTRAL TIMOR DISTRICT - Nalle, Frederic Winston; Duli , Dominikus Kopong; Amteme , Charles (Jurnal AGRISEP, 2022)
Inclusive economic development  prioritizes equity in order to realize economic justice for all. Therefore, each local government is expected to be able to optimize the leading sector so that it can act as the locomotive of the regional economy. This study aims to determine changes and shifts in the economic sector and then formulate appropriate strategies in developing leading sectors in realizing quality development in North Central Timor Regency. The analytical tools used are Shift Share analysis, Klassen typology and SWOT analysis. The type of data used is primary data for the needs of SWOT analysis and secondary data for the needs of shift share analysis and classification typology, especially GRDP and Employment data per sector from 2015-2020. The results of the study show that the agricultural sector is the leading sector because it has the largest contribution value in the formation of GRDP but on the other hand it also holds various poverty problems in it. From these conditions, the results of the SWOT Analysis recommend the right policy in an effort to realize inclusive development is the Strength–Opportunity (SO) Strategy where the government is expected to take advantage of the strengths of the agricultural sector by looking at all aspects of the opportunities that exist.